2023
DOI: 10.1109/tvt.2022.3208268
|View full text |Cite
|
Sign up to set email alerts
|

Active RIS-Assisted Secure Transmission for Cognitive Satellite Terrestrial Networks

Abstract: How to cite:Please refer to published version for the most recent bibliographic citation information. If a published version is known of, the repository item page linked to above, will contain details on accessing it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 28 publications
0
26
0
Order By: Relevance
“…Mounting an LED light display on different parts of the vehicle (e.g., on the windscreen), as well as using different communication patterns, are also potential future research directions. Data collection and transmission might include recent advances in sensing techniques as well, such as reconfigurable intelligent surface [ 30 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mounting an LED light display on different parts of the vehicle (e.g., on the windscreen), as well as using different communication patterns, are also potential future research directions. Data collection and transmission might include recent advances in sensing techniques as well, such as reconfigurable intelligent surface [ 30 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The constraints of minimum quality-ofservice (QoS) is applied, and a sum-rate maximization problem is formulated and solved. In [13], the cognitive satellite terrestrial network and a secure transmission maximization problem is considered. A interference threshold is considered which introduces larger non-convexity of the problem.…”
Section: A Related Workmentioning
confidence: 99%
“…In this paper, we develop the beamforming optimization of this problem, and apply the mainstream AO method to solve this problem. It is possible the our work can be extended to more general scenarios or the complexity of the optimization can be reduced by referring to previous works [12], [13], [14], [15], [16], [17], [18], [19].…”
Section: A Related Workmentioning
confidence: 99%
“…By converting direct current bias power into radio frequency power, the active element can directly amplify the incident signal [37]. Then, in [38], the authors considered the effect of active RIS in improving the achievable secrecy rate of cognitive satelliteterrestrial network. In [39], the authors studied the active RISenabled energy-constrained wireless network and showed the superiorities of the active RIS in supporting multiple energylimited devices.…”
Section: Introductionmentioning
confidence: 99%